Changes in land use (2008 - 2018) on Avenida Prefeito Roque Vernalha, Paranaguá, Paraná - Furuzawa, Marcos; Pires, Christian; Luis Tonetti, Emerson (Technical and Scientific Journal Green Cities, 2022)
Monitoring changes in urban land use is a way to avoid changes in the quality of the environment that can be detrimental to human well-being. This research work aimed to analyze the changes in uses along Avenida Prefeito Roque Vernalha in the urban area of the municipality of Paranaguá, in the coastal region of Paraná, in the years 2008 and 2018. For this, in front of each lot, it was reclassification carried out in 2018, based on the survey carried out in 2008, of the uses: spaces for public use and free from buildings, residential, vacant land, less potential to cause pollution, greater potential to cause pollution. The three initial classes were considered reference points for good environmental quality and, therefore, only the lots with commercial and industrial/port uses received pollution potential. After collection, the data were entered into a spreadsheet to compare the variation in uses. The results showed that there was no change in the number of lots. There was an increase of 13.3% in the classes of uses with lesser and greater potential to cause pollution and an equal reduction in the group of other classes. The temporal analysis of the studied landscape indicates a potential change in the quality of the environment. This result can contribute to future management proposals in the municipality, considering the synergy of inadequate and incompatible uses with residential and public use spaces free of buildings. Keywords: Land use. Environmental Quality. Urban landscape planning.